Identitas Dakwah Perempuan dengan Techno-Religion - Pambayun, Ellys Lestari (El Madani: Jurnal Dakwah dan Komunikasi Islam, 2020)
The issue that is the focus of this paper is the phenomenon of identity formation that is built through da'wah conveyed by women on social media, such as the Gender Studies Community (Ustazah Nur Rodiah), the Niqab Squad (Indardari and Dina Nurlina), and Mumpuni Handayekti. The ustazahs who understand Islam seem to be a reference for the public because of their understanding and mastery of verses, hadiths, religious studies, and interpretations which are the content of their platforms at any time. On the one hand, the convenience of social media as a source of da'wah content has triggered the emergence of "millennial ustazah identity" as the spirit of women to ground the da'wah movement. On the other hand, being a "religious agent" that positions women as preachers still gets stereotypes from the dominant environment. These activities of KGI, Niqab Squad, and Mumpuni Handayekti attempt to be studied through the conceptual approaches of Technoreligion, Gender Communication Identity, and Helena Cixous Writing Feminist Criticism. This study uses the netnography method on three da'wah content on YouTube, Instagram, and Facebook. The results of the study provide findings that in the technology concept, social media has the potential to expand and structure the religious behavior of KGI, Niqab Squad and Mumpuni Handayekti preachers as part of millennial society Especially in obtaining messages and religious identity of these preachers in the concept of Gender Communication Identity, explaining that the formation of their identity on social media: KGI (youtube and instagram), Niqab Squad (youtube, instagram, facebook), and Mumpuni Handayekti (youtube) can be traced through I and Me characters who are awakened through their behavior or symbolic activities with the mad'u (audience). And, in the perspective of Hélène Cixous explains that the formation of the identity of "millennial ustazah" indicates a sexist and ideological structure: KGI (identity: critical and scientific studies), Niqab Squad (identity: stylist and millennial), and Mumpuni Handayekti (identity: local feminine). assumed to have independence, authenticity, transformation, and strength of its own. Although they have their own uniqueness and strengths that masculine don't have: sharpness of taste and language that is different from men's (language that emerges from the media).